Teknologi Modifikasi Tepung Kasava - Haryadi Haryadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2011)
Cassava productivity is very potential to support food security. Processing of cassava into flour makes the food more durable, less voluminous and easier to handle, and flexible to cook. To extend the use of cassava flour, it is necessary to develop technology to produce quality cassava flour suitable for various food purposes. A certain flour finess is desired to free the starch granules and to allow the granule’s cooking characteristics to express significantly. Modification of cassava flour technology may involve physical, biological, chemical aspects, as well as combination of the aspects.ABSTRAKPotensi produksi kasava sangat besar untuk dimanfaatkan sebagai pendukung ketahanan pangan. Pengolahannya men jadi tepung memungkinkan lebih awet, lebih ringkas dan lebih mudah diangkut, serta lebih luwes untuk diolah. Untuk memperluas penggunaan tepung kasava, perlu pengembangan teknologi produksi tepung bermutu yang dapat diman faatkan dalam berbagai olahan makanan. Tepung dikehendaki pada kelembutan tertentu, sehingga granula-granula pati terlepas dari jaringan awalnya, dan selanjutnya ciri-ciri granula dalam pemasakan menjadi nyata. Modifikasi pembuatan tepung kasava dapat dilakukan secara fisik, biologis maupun kimiawi, ataupun gabungan dari aspek-aspek tersebut.